Late Onset Hepatic Encephalopathy after Living Donor Liver Transplant: Successful Reversal by Plug Embolization of Shunt—A Report of Two Cases - Shahnawaz Bashir; Dibyalochan Praharaj; Adnan Khan; Subhash Gupta; Pragati Gakher (Journal of Clinical Interventional Radiology ISVIR)
In liver transplant (LT) recipients, development of portosystemic (PS) shunts can lead to hepatic encephalopathy. Here we report the cases of two patients who presented with hepatic encephalopathy 11 and 15 years after LT. Plug-assisted embolization of PS shunt led to significant improvement in their clinical and neurological symptoms, highlighting the importance of monitoring for PS shunts in long-term LT follow-up.